Who Knows! - Enric Fernández Gel (TheoLogica)
According to the Evil-God challenge, there is an epistemic symmetry between the hypothesis of a Good God and the reverse hypothesis of an Evil God. Hence, belief in a Good God is no more reasonable than belief in an Evil God. Several persuasive responses have been offered to this challenge, but in this paper I focus on one that, to my mind, is underdeveloped in the literature; namely that the Evil God hypothesis casts serious doubt on the reliability of our cognitive faculties, while no comparable thing can be said of the Good God hypothesis, in any case not to the same degree of plausibility. Assuming an apparently innocuous rationality principle, this breaks the supposed symmetry between the two hypotheses and gives the theist reason enough to justifiably prefer the latter.